2022
DOI: 10.1038/s41598-022-25216-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous protein networks around ANG2 and VEGF in proliferative diabetic retinopathy and the differential effects of aflibercept versus bevacizumab pre-treatment

Abstract: Extracellular signalling proteins interact in networks rather than in isolation. In this context we investigated vitreous protein levels, including placental growth factor (PlGF), angiopoietin-2 (ANG2) and vascular endothelial growth factor (VEGF), in patients with proliferative diabetic retinopathy (PDR) with variable disease severities, and after anti-VEGF pre-treatment. Vitreous samples of 112 consecutive patients undergoing vitrectomy for PDR and of 52 non-diabetic patients with macular holes as controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Eyes with active PDR exhibited higher Ang2 levels than inactive PDR. Furthermore, the levels of Ang2 correlated with those of VEGF [170]. Another cross sectional study reported that in eyes with PDR, Ang1, Ang2, VEGF-A, PlGF, Il-8 and Il1b were all elevated when compared to non-diabetic eyes [171].…”
Section: Diabetic Patients and Ang-tie Signalingmentioning
confidence: 89%
“…Eyes with active PDR exhibited higher Ang2 levels than inactive PDR. Furthermore, the levels of Ang2 correlated with those of VEGF [170]. Another cross sectional study reported that in eyes with PDR, Ang1, Ang2, VEGF-A, PlGF, Il-8 and Il1b were all elevated when compared to non-diabetic eyes [171].…”
Section: Diabetic Patients and Ang-tie Signalingmentioning
confidence: 89%
“…Vascular endothelial growth factor A (VEGF-A), higher levels of which are present in the vitreous of patients with DR, DME, or RVO, elevates the permeability of the retinal endothelium, playing a key role in the pathophysiology of macular edema (3)(4)(5)(6)(7). Higher concentrations in the vitreous or aqueous humor of inflammatory cytokines, such as interleukin (IL)-6 and IL-1β are not only associated with the pathogenesis of RVO, respectively, but also with the development of DME and proliferative DR (8)(9)(10)(11)(12). Additionally, the ocular renin-angiotensin aldosterone-system (RAAS) also regulates the retinal blood and fluid balance; several studies point to its major role in the development of DME (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%